Effect of a nurse-led individualized self-management program for Chinese patients with acute myocardial infarction undergoing percutaneous coronary intervention. (1st April 2020) - Jiang, Wenhui; Feng, Mei; Gao, Chunyan; Li, Juanli; Gao, Rui; Wang, Wenru
Abstract: Background: The study of the development and evaluation of self-management intervention among patients with acute myocardial infarction (AMI) undergoing percutaneous coronary intervention (PCI) is lacking, especially in China. Aim: To examine the effects of a nurse-led individualized self-management program (NISMP) on health behaviors, control of cardiac risk factors, and health-related quality of life (HRQoL) among patients with AMI undergoing PCI. Methods: The quasi-experimental design included a convenience sample of 112 participants recruited from a tertiary hospital in China. The participants were assigned to the control group ( n = 56) or the intervention group ( n = 56). The intervention group underwent the NISMP, which includes six group-based education sessions, a face-to-face individual consultation, and 12-month telephone follow-ups. Data were collected at baseline and at the end of the 12-month program using the Health Promotion Lifestyle Profile, the Risk Factors Assessment Form, and the Short Form 36-item Health Survey. Results: The baseline sociodemographic and clinical characteristics of the two groups were comparable ( p > 0.05). After the 12-month intervention, the health behaviors and HRQoL of the participants in the intervention group had significantly improved ( p < 0.05 for both) compared to those of the control group. Compared to the control group, the participants in the intervention group also reported significantly better control of cardiac risk factors including smoking (χ 2 = 4.709, p = 0.030), low-density lipoprotein (χ 2 = 4.160, p = 0.041), body mass index (χ 2 = 3.886, p = 0.049) and exercise (χ 2 = 10.096, p = 0.001). Conclusion: The NISMP demonstrated positive effects on health behaviors, control of cardiac risk factors, and HRQoL among Chinese patients with AMI undergoing PCI.